Teaching Skill Performance of Sixth Semester Students of English Education Program Merangin University - Hartati, Hera; Ningsih, Retno Wahyu; Oktawati, Herysa (Universitas Batanghari Jambi, 2022)
The purpose of this research was to describe about students’ teaching skill in micro teaching class of English Education Program. Micro teaching as the course to prpere them to be a professional teacher.The teaching skill needs by the senventh semester student before conduct Practice Teaching in some schools around the Merangin regency This reasearch was descriptive quantitave research. It was conducted in English Educational Program of Teacher Training and Education Faculthy Merangin University. The population was the seventh semester students consists of two class, it consisted of 28 students . It used purposive sampling. The researcher use observation sheet and field notes as the instruments of collecting data. In doing this research, the researcher analyzed the data by connecting between the indicator of teaching skills (opening and closing the lesson, explaining the lesson, questioning skill, guiding group and individual, giving motivation, giving variation, using media and appropriate strategy, managing the class) that covered on observation sheet and students performance or practice teaching in micro teaching class. Those teaching skills observed by the another students (audience) while the students practice them. The lecturer also observed the students in implementing those teaching skill. In filling the observation uses Likert’s Scale. Based on the result of the research, it can be concluded that from seventh indicator, students have highest skill in explaining skill and the lowest skill in opening and closing the lesson. From 30 sub indicators, they have lowest skill in giving variation of reinforcement and the highest skill in simple and clear explanation. In order to further students improve teaching skill especially can master or practice well about those seventh components. It ia a basic for teacher candidate before to be the real teacher.